The Clonic Phase of Seizures in Patients Treated with Electroconvulsive Therapy is Related to Age and Stimulus Intensity - Tseng, Chih-Chieh (Frontiers in Psychiatry, 2013)
Background: Electroconvulsive therapy (ECT) is effective in the treatment of major depressive disorder and schizophrenia in patients who are drug-naïve or less-receptive to antipsychotic drugs. Several studies have discussed the correlation between patient characteristics, input current volume and seizure duration. According to the present principle of ECT guidelines, the therapeutic effect of ECT mostly correlates with seizure duration. As the tonic phase is different from the clonic phase with respect to brain function and activity, it is informative to analyse both the tonic and clonic phases. Thus, this study sought to clarify the relationship between the features of the two phases, and to re-examine and refine guidelines regarding ECT treatment. Method: ECT-course data from 44 schizophrenia patients were recollected, including the number of treatments that they had received, their gender, age, and the association of these characteristics with motor seizure duration was analysed. A two-factor correlation was employed to test the relationship between each of the two factors. Result: The meta-analysis results indicate that seizure duration and age are significantly correlated. Older patients had relatively short seizure durations after ECT-treatment. Notably, a negative correlation was only found between age and the clonic phase of the seizure, not between age and the tonic phase. Furthermore, this study also found an inverse relationship between ECT-intensity and the clonic phase, but not between ECT-intensity and the tonic phase. Conclusion: This study demonstrated that age and ECT-intensity are negatively correlated with seizure duration, particularly in the clonic phase. The present observations are not fully consistent with the basic guidelines of the APA-ECT practical manual. Accordingly, the predictions regarding the therapeutic effect of ECT can be based on both the seizure duration and the clonic phase.